A carbon-fixing early-strength clinker-free low-carbon cementitious material and a method of using the same
By using calcined clay and calcium hydroxide components in clinker-free cementitious materials and introducing CO2 gas during the stirring process, the problem of carbon emissions in the cement industry and insufficient strength of clinker-free cementitious materials in the early stage is solved, and the problem of insufficient strength of clinker-free cementitious materials is achieved. It has efficient CO2 recycling and intensity improvement, and has significant social and ecological benefits and market application prospects.
Patent Information
- Application Number
- CN202310303557.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-23
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-03-23
AI Technical Summary
The carbon emission problems in the existing cement industry and the problem of low early strength of clinker-free cementitious materials, especially the CO2 emissions caused by cement production have not been significantly improved.
Calcined clay and calcium hydroxide components are used to replace cement. By introducing CO2 gas into the stirring process and reacting with calcium hydroxide components, calcium carbonate particles are generated, which promotes the formation of C-A-S-H gel, improves early strength, and is calcined. The volcanic ash reaction of clay with calcium hydroxide provides long-term strength.
It has achieved low-cost and low-energy consumption of CO2 recycling, significantly improved the early and long-term strength of clinker-free gelling materials, reduced CO2 emissions and energy consumption of raw material production, and has the significance of green and sustainable development.
Smart Images

Figure CN116354625B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a carbon-fixing early-strengthening clinker-free low-carbon cementitious material and a use method thereof. Background Art
[0002] At present, the main methods of CO2 capture include pre-combustion capture, post-combustion capture and industrial process capture. At the same time, the main methods of CO2 reuse include mineral carbonization, biological breeding and ocean storage. The existing CO2 capture and reuse methods can effectively capture and consume part of CO2, but there are problems such as high investment cost, high energy consumption and complex production line.
[0003] As of 2020, the total carbon emissions of the building materials industry reached 1.375 billion tons, second only to the power generation and steel industries, of which the cement industry's carbon emissions accounted for more than 80% of the building materials industry's carbon emissions. It can be seen that solving the problem of carbon emissions in the cement industry is the top priority in solving the carbon emissions in the building materials industry.
[0004] Therefore, the organic combination of CO2 capture and disposal with energy conservation and emission reduction in the cement industry can achieve low-cost, large-scale treatment of CO2, which is of great significance to the green and sustainable development of the building materials industry.
[0005] Compared with traditional auxiliary cementitious materials such as fly ash and slag, calcined clay has the advantages of wide distribution of raw materials, abundant reserves, simple preparation process and low energy consumption. Domestic and foreign researchers believe that the limestone-calcined clay-cement ternary cementitious material system formed by partial replacement of cement by calcined clay and limestone powder has good development prospects. In this ternary cementitious material system, cement provides an alkaline environment through hydration, and limestone provides additional carbonates, realizing the coupling effect of hydration reactions in the system and promoting the development of mechanical properties and durability. However, there are corresponding problems in this system. On the one hand, the early strength is significantly affected by the reaction degree of calcined clay and the content of inert filler limestone. On the other hand, the carbon emissions caused by cement production have not been significantly improved. Summary of the invention
[0006] The purpose of the present invention is to overcome the above technical deficiencies, provide a carbon-fixing early-strength clinker-free low-carbon cementitious material and a method of using the same, and solve the technical problems in the prior art of low early strength of clinker-free cementitious material systems and the need to use cement to cause CO2 emissions.
[0007] In order to achieve the above technical purpose, the technical solution of the present invention provides a carbon-fixing early-strengthening clinker-free low-carbon cementitious material:
[0008] The raw materials include calcined clay and calcium hydroxide components, and the mass ratio of the calcined clay to the calcium hydroxide components is (7-5): (3-5).
[0009] Furthermore, the calcined clay is obtained by calcining a clay raw material, wherein the kaolin content in the clay raw material is 30% to 100%.
[0010] Furthermore, the calcium hydroxide component includes carbide slag, papermaking white mud or pure calcium hydroxide.
[0011] Furthermore, the Ca(OH)2 content in the calcium hydroxide component is between 60% and 100%.
[0012] The technical solution of the present invention also provides a method for using a carbon-fixing early-strength clinker-free low-carbon cementitious material, comprising the following steps:
[0013] (1) taking calcined clay and calcium hydroxide components in proportion, adding them into a blender and mixing them to obtain a gelling component;
[0014] (2) adding water and a water reducing agent to the gelling component, sealing the mixer after mixing, and introducing CO2 gas into the mixer under stirring conditions; stopping stirring after mixing evenly, and simultaneously stopping introducing CO2 gas to obtain a mixture;
[0015] (3) The mixture is cast into shape, and after solidification, the mold is removed and cured to obtain a carbon-fixing early-strength clinker-free low-carbon cementitious material specimen.
[0016] Furthermore, in step (2), water and a water reducing agent are added and mixed for 3 to 15 seconds; CO2 is introduced and stirred for 2 to 5 minutes; the concentration of the introduced CO2 gas is 50% to 100%.
[0017] Furthermore, in step (2), the mass ratio of water to gelling component is (0.4-0.7):1.
[0018] Furthermore, in step (2), the mass ratio of the water reducing agent to the gelling component is (0.02-0.03):1.
[0019] Furthermore, in step (2), the water reducing agent is a polycarboxylic acid water reducing agent, with a solid content of ≥60%, an air content of ≤4.0%, and a water reduction rate of ≥35%.
[0020] Furthermore, in the mixture of step (2), calcium carbonate particles with a particle size of 10 nm to 100 nm are generated on the surface of the calcium hydroxide component.
[0021] Compared with the prior art, the beneficial effects of the present invention include:
[0022] 1. The carbon-fixing early-strengthening clinker-free low-carbon cementitious material provided by the present invention has a volcanic ash reaction between the calcium hydroxide component in the raw material and the calcined clay to generate products such as CASH gel, which can continuously provide a source of strength for the low-carbon clinker-free cementitious material and corresponding products.
[0023] 2. When the carbon-fixing, early-strength, clinker-free, low-carbon cementitious material provided by the present invention is used, a mixing method of introducing CO2 while stirring is adopted. During the stirring process, it is only necessary to keep the stirrer closed, and there is no need to use physical and chemical means such as pressurization, heating or the use of chemical admixtures to promote the dissolution and reaction of CO2 gas. It has the characteristics of easy operation, low cost and low energy consumption, and is conducive to the construction of subsequent production facilities.
[0024] 3. When the carbon-fixing early-strength clinker-free low-carbon cementitious material provided by the present invention is used, CO2 gas is introduced into the mixer to react with Ca(OH)2 in the calcium hydroxide component to form carbonate (mainly calcium carbonate), the reaction process is stable, and the CO2 absorption rate is high. The formed calcium carbonate reacts with the active aluminum phase in the calcined clay to form carbon aluminate, which has a role in improving the structure refinement and compaction, and effectively realizes the recycling of CO2 gas.
[0025] 4. At the same time, after the CO2 gas is introduced into the mixer, it reacts with the calcium hydroxide component in the gelling component to form nano-sized granular calcium carbonate on the surface of the calcium hydroxide component, providing additional nucleation sites for the formation of CASH gel, promoting the formation of CASH gel in the early stage of the hydration reaction system, and achieving relatively excellent early strength development. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the XRD spectrum of the mixture of Examples 1 to 3 of the present invention;
[0027] Figure 2 is the SEM image of calcium carbonate in the mixture of Examples 1 to 3 of the present invention;
[0028] Figure 3 3d, 7d and 28d compressive strength of Comparative Examples 1 to 3 and Examples 1 to 3;
[0029] FIG4( a ) is a curve showing the change of the unit heat release rate (normalized to the gelling material) over time for Comparative Examples 1 to 3 and Examples 1 to 3;
[0030] FIG. 4( b ) is a curve showing the cumulative heat release (normalized to the gelling material) of Comparative Examples 1 to 3 and Examples 1 to 3 as a function of time. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0032] The present invention provides a carbon-fixing early-strengthening clinker-free low-carbon cementitious material and a preparation method thereof, wherein calcined clay and calcium hydroxide components are used to completely replace cement as the cementitious material composition, thereby significantly reducing the raw material production cost and the energy consumption and CO2 emissions generated during the preparation process. By introducing CO2 gas during the stirring of the raw materials, nano-sized calcium carbonate particles are generated on the surface of the calcium hydroxide component, and the nano-calcium carbonate particles provide early strength for the system through nucleation effect and chemical reaction, while the volcanic ash reaction of calcined clay and calcium hydroxide provides long-term strength development for the system.
[0033] The raw materials of the carbon-fixing early-strength clinker-free low-carbon cementitious material of the present invention mainly include calcined clay and calcium hydroxide components, and the mass ratio of calcined clay to calcium hydroxide components is (7-5): (3-5). Within this range, the calcined clay can react to a high degree in the alkaline environment provided by the calcium hydroxide component, and the obtained product has high mechanical properties.
[0034] Preferably, the kaolin content (hereinafter, all contents by mass unless otherwise specified) in the clay raw material for producing calcined clay is between 30% and 100%, and more preferably between 50% and 100%.
[0035] Preferably, the calcined clay is purchased from China National Materials International Engineering Co., Ltd.
[0036] Preferably, the calcium hydroxide component includes carbide slag, papermaking white mud or pure calcium hydroxide.
[0037] Preferably, the Ca(OH)2 content in the calcium hydroxide component is between 60% and 100%, and more preferably between 80% and 100%.
[0038] Preferably, in the gelling material of the present invention, the mass ratio of calcined clay to calcium hydroxide component is (5.5-6):(4.5-4), more preferably (1.35-1.45):1, and most preferably 1.4:1.
[0039] The method for using the carbon-fixing early-strengthening clinker-free low-carbon cementitious material of the present invention comprises the following specific steps:
[0040] The first step is to weigh calcined clay, calcium hydroxide component, water and water reducing agent according to the composition of each raw material;
[0041] The second step is to add the weighed calcined clay and calcium hydroxide components into a mixer and mix for 10 to 60 seconds;
[0042] The third step is to add the weighed water reducer into water and mix;
[0043] The fourth step is to add the mixture of water and water reducing agent into a mixer and mix for 3 to 15 seconds to make the water and water reducing agent evenly mixed.
[0044] Step 5: introduce CO2 gas into the mixer, and keep the mixer sealed and stirred during the introduction process;
[0045] Step 6: After the mixer is mixed, the stirring is stopped and the introduction of CO2 gas is stopped to obtain a mixture;
[0046] The seventh step is to pour the mixture into a mold, let it stand for 1 day, then demould it and place it in a standard curing room for curing to obtain a carbon-fixing early-strength clinker-free low-carbon cementitious material specimen.
[0047] In the present invention, the gelling component is composed of calcined clay and calcium hydroxide component.
[0048] Preferably, the mass ratio of water to gelling component is (0.4-0.7):1, and more preferably 0.6:1.
[0049] Preferably, the mass ratio of the water reducing agent to the gelling component is (0.02-0.03):1, and more preferably 0.025:1.
[0050] Preferably, the water reducing agent is a polycarboxylic acid water reducing agent, with a solid content of ≥60%, an air content of ≤4.0%, and a water reduction rate of ≥35%.
[0051] Preferably, the stirring time after the CO2 is introduced into each raw material is between 2 and 5 minutes.
[0052] Preferably, the concentration of the introduced CO2 gas is between 50% and 100%, preferably between 80% and 100%.
[0053] After the CO2 gas is introduced into the present invention, calcium carbonate particles are generated on the surface of the calcium hydroxide component. After testing the mixture, the mass content of calcium carbonate is between 10% and 20%, and more preferably 17 to 18%. The size of the calcium carbonate particles is between 10nm and 100nm.
[0054] The present invention uses calcined clay and calcium hydroxide components as the main components, introduces CO2 as a carbon fixation method, and obtains a green cementitious material with good early strength performance; the carbon-fixing early strength clinker-free low-carbon cementitious material obtained by the present invention can be used in building materials, completely replacing cement as a cementitious material, and providing excellent early strength.
[0055] The present invention is further described in detail below through specific examples and comparative examples.
[0056] To avoid redundancy, in the following embodiments and comparative examples of the present invention, unless otherwise specified, a carbon-fixing early-strengthening clinker-free low-carbon cementitious material and a method of using the same are as follows:
[0057] (1) mixing the calcined clay and the calcium hydroxide component in the proportion for 30 seconds to obtain a gelling component;
[0058] (2) Add water and water reducing agent to the gelling component and mix for 5 seconds; then, introduce CO2 gas into the mixer during the stirring process; keep the mixer sealed during the introduction process and stir for 3 minutes; stop stirring after the mixer has mixed for 3 minutes, and stop introducing CO2 gas at the same time to obtain a mixture.
[0059] (3) The mixture is poured into a mold to form a carbon-fixed early-strength clinker-free low-carbon cementitious material specimen.
[0060] Among them, the kaolin content in the calcined clay raw material used is 50%; the calcium hydroxide component used is analytical pure Ca(OH)2; the water reducer used is polycarboxylic acid water reducer with a solid content of 60%; the concentration of CO2 gas introduced during stirring is 90%; and the time for introducing CO2 gas is 3 minutes.
[0061] In Examples 1-3, calcined clay and calcium hydroxide components are mixed, the mass ratio of calcined clay to calcium hydroxide components is 7: (3-7), the water-binder ratio is 0.6, and 2.5% of the solid mass of polycarboxylic acid water reducer is added to ensure good fluidity of the slurry. Compared with Examples 1-3, the difference between Comparative Examples 1-3 is that CO2 is not introduced during the stirring process. The specific raw material dosage ratio is shown in Table 1.
[0062] Table 1 Raw material dosage ratio of the present invention and comparative examples
[0063]
[0064] Figure 1 2 is the XRD spectrum of the mixture of Examples 1 to 3. It can be seen from the figure that after the introduction of CO2, obvious characteristic peaks of calcium carbonate were observed in Examples 1 to 3, indicating that calcium carbonate was generated in the system.
[0065] In order to determine the content of calcium carbonate generated in Examples 1 to 3 after the introduction of CO2, the mixtures of Examples 1 to 3 were tested by comprehensive thermal analysis. The calcium carbonate content was calculated by the following formula based on the loss on ignition between 600°C and 800°C, and the calculation results are listed in Table 2.
[0066]
[0067] Table 2 Calcium carbonate content in the mixture of Examples 1 to 3
[0068]
[0069] In order to determine the morphology and size of the calcium carbonate generated in Examples 1 to 3 after the introduction of CO2, a field emission scanning electron microscope was used to photograph the microscopic morphology of the mixture to obtain its SEM image, see Figure 2 .
[0070] from Figure 2 It can be seen that in Examples 1 to 3, after CO2 was introduced during the stirring process, calcium carbonate particles with a size of about 50 nm were generated on the surface of the calcium hydroxide component and were relatively evenly distributed on the observed plate-like Ca(OH)2 surface.
[0071] Mechanical properties test The compressive strength test was carried out in accordance with GB / T17671 1999 "Test method for strength of cement mortar". The test results are shown in Figure 3 .
[0072] from Figure 3 It can be seen that the compressive strength of Examples 1 to 3 at 3d is significantly higher than that of Comparative Examples 1 to 3, respectively, indicating that a large amount of hydration products are generated in Examples 1 to 3 at an early stage and contribute to the strength. On the one hand, it is because nano calcium carbonate particles are generated on the surface of the calcium hydroxide component, which promotes the formation of CASH gel on its surface by providing additional nucleation sites; on the other hand, in the alkaline environment provided by the calcium hydroxide component, the calcium carbonate on the surface of the calcium hydroxide component reacts with the active aluminum in the calcined clay to form carbon aluminate. Under the joint action of the two, the system forms a richer and denser hydration product composition than Comparative Examples 1 to 3 at an early stage, so that Examples 1-3 have considerable early strength. In addition, the compressive strength of Examples 1 to 3 at 7d and 28d are higher than that of Comparative Examples 1 to 3, indicating that the introduction of CO2 during the mixing process promotes the development of later strength, as shown in Table 3.
[0073] Table 3 3, 7 and 28 day compressive strength (MPa) of Examples 1 to 3 and Comparative Examples 1 to 3
[0074]
[0075] At the same time, combined with the test results of Examples 1 to 3, it can be seen that the amount of calcium hydroxide component in the gelling component of the present invention cannot be too much and cannot exceed the amount of calcined clay; the mass ratio of calcined clay to calcium hydroxide component of the present invention is preferably (7-5): (3-5), and further preferably (5.5-6): (4.5-4). The present invention controls the mass ratio of calcined clay to calcium hydroxide component, and then introduces carbon dioxide during the mixing process. The two can produce a synergistic effect on improving the early strength of the obtained test piece, with a 3d compressive strength of 8.71-15.87MPa, a 7d compressive strength of 13.26-20.61MPa, and a 28-day compressive strength of 23.61-30.14MPa.
[0076] The hydration heat test of Examples 1 to 3 and Comparative Examples 1 to 3 was carried out according to the mix ratio using a TAM, and the results are shown in Figures 4(a) and 4(b).
[0077] As can be seen from Figure 4 (a) and Figure 4 (b), compared with Comparative Examples 1 to 3, Examples 1 to 3 have more obvious hydration exotherms in 0-240h, and obvious hydration exothermic peaks appear. The hydration exothermic peaks of Examples 1 to 3 are all hump-shaped rather than obvious peaks, indicating that different reaction processes are involved in the exothermic process, namely, the process of calcium carbonate reacting with the active aluminum phase in the calcined clay to form carbon aluminate and the process of calcium hydroxide reacting with the active aluminum phase in the calcined clay to form CASH gel. Comparative Examples 1 to 3 did not show obvious hydration exothermic peaks in 0-240h. The hydration exothermic rate began to rise after 90h, but the rising rate was slow. The increase in the hydration exothermic rate corresponded to the reaction between calcium hydroxide and the active aluminum phase in the calcined clay. Similar to the hydration exothermic rate, Examples 1 to 3 have higher cumulative hydration exothermic heat in 0-240h. The above shows that the introduction of CO2 during the mixing process significantly accelerates the hydration reaction rate of the clinker-free cementitious material, achieving the development of early strength and long-term strength.
[0078] The present invention discloses a carbon-fixing early-strengthening clinker-free low-carbon cementitious material and a method for using the same. Calcined clay and calcium hydroxide components are used to completely replace cement, and CO2 is introduced during the mixing of the raw materials. On the basis of providing the alkaline environment required for the calcined clay reaction, additional carbonates are generated by the reaction of the calcium hydroxide component with CO2, thereby promoting the formation of calcium aluminosilicate hydrate (CASH) gel, which is the main source of strength in the aluminum-rich system, and the synergistic reaction between the active aluminum phase and the carbonate, thereby achieving the development of early strength and long-term mechanical properties of the clinker-free low-carbon cementitious material. The present invention effectively realizes the organic combination of low-carbon production and efficient utilization of CO2 in the building materials industry, and has high social and ecological benefits and market application prospects.
[0079] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A carbon-fixing early-strength clinker-free low-carbon cementitious material, characterized in that: The raw material consists of calcined clay and calcium hydroxide components, and the mass ratio of calcined clay to calcium hydroxide components is (5.5-6): (4.5-4); The calcined clay is obtained by calcining a clay raw material, wherein the kaolin content in the clay raw material is 30% to 100%; The calcium hydroxide component includes carbide slag, papermaking mud or pure calcium hydroxide; The Ca(OH)2 content in the calcium hydroxide component is between 60% and 100%.
2. The method for using the carbon-fixing early-strength clinker-free low-carbon cementitious material according to claim 1, characterized in that: The following steps are involved: (1) Calcined clay and calcium hydroxide components are added into a mixer according to a certain proportion to obtain a gelling component; (2) adding water and a water reducing agent to the gelling component, sealing the mixer after mixing, and introducing CO2 gas into the mixer under stirring conditions; stopping stirring after the mixture is evenly mixed, and simultaneously stopping introducing CO2 gas to obtain a mixture; (3) The mixture is cast into shape, and after solidification, the mold is removed and cured to obtain a carbon-fixing early-strength clinker-free low-carbon cementitious material specimen.
3. The method for using the carbon-fixing early-strength clinker-free low-carbon cementitious material according to claim 2, characterized in that: In step (2), water and a water reducing agent are added and mixed for 3 to 15 seconds; CO2 is introduced and stirred for 2 to 5 minutes; the concentration of the introduced CO2 gas is 50% to 100%.
4. The method for using the carbon-fixing early-strength clinker-free low-carbon cementitious material according to claim 2, characterized in that: In step (2), the mass ratio of water to gelling component is (0.4-0.7):
1.
5. The method for using the carbon-fixing early-strength clinker-free low-carbon cementitious material according to claim 2, characterized in that: In step (2), the mass ratio of the water reducing agent to the gelling component is (0.02-0.03):
1.
6. The method for using the carbon-fixing early-strength clinker-free low-carbon cementitious material according to claim 2, characterized in that: In step (2), the water reducing agent is a polycarboxylic acid water reducing agent with a solid content of ≥60%, an air content of ≤4.0%, and a water reduction rate of ≥35%.
7. The method for using the carbon-fixing early-strength clinker-free low-carbon cementitious material according to claim 2, characterized in that: In the mixture of step (2), calcium carbonate particles with a particle size of 10 nm to 100 nm are generated on the surface of the calcium hydroxide component.
